2005
DOI: 10.1161/01.atv.0000167525.69400.9c
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Bacteremia Induces Coronary and Aortic Atherosclerosis in Normocholesterolemic and Hypercholesterolemic Pigs

Abstract: Objectives-The aim of this study was to determine whether recurrent intravenous injections with Porphyromonas gingivalis (P gingivalis), mimicking periodontitis-associated bacteremia, promotes coronary artery and aortic atherosclerosis in pigs. Methods and Results-Pigs (nϭ36) fed low-or high-fat chow were divided into P gingivalis-sensitized and P gingivalis-challenged groups or P gingivalis-sensitized controls and saline-treated controls. Pigs were sensitized with 10 9 killed P gingivalis subcutaneously. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
134
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(136 citation statements)
references
References 58 publications
1
134
1
Order By: Relevance
“…Periodontal pathogens, such as Aggregatibacter actinomycetemcomitans, Treponema denticola and Porphyromonas gingivalis are also capable of invading endothelial cells [2327], and they have been detected in atherosclerotic plaques, heart valves, aortic aneurysms, carotid and coronary vessels [2833]. Studies in a variety of animal models have demonstrated that recurrent bacteraemia or oral administration with P. gingivalis can enhance atherogenesis [34,35]. Of interest, P. gingivalis is so far the only bacterium capable of causing enzymatic citrullination of peptides with subsequent development of anti-citrullinated peptide auto-antibodies, a major etiopathologic event in RA [36].…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal pathogens, such as Aggregatibacter actinomycetemcomitans, Treponema denticola and Porphyromonas gingivalis are also capable of invading endothelial cells [2327], and they have been detected in atherosclerotic plaques, heart valves, aortic aneurysms, carotid and coronary vessels [2833]. Studies in a variety of animal models have demonstrated that recurrent bacteraemia or oral administration with P. gingivalis can enhance atherogenesis [34,35]. Of interest, P. gingivalis is so far the only bacterium capable of causing enzymatic citrullination of peptides with subsequent development of anti-citrullinated peptide auto-antibodies, a major etiopathologic event in RA [36].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of P. gingivalis are detected in periodontal lesions, and these can be significantly reduced following successful periodontal therapy (Cappelli et al, 2009;Salvi et al, 1997;Socransky et al, 2002;Ximenez-Fyvie et al, 2000;Yamazaki et al, 2004). Apart from its well accepted role as an oral pathogen in the establishment of chronic inflammation at the site of infection, there is increasing evidence of a link between P. gingivalis-associated periodontal disease and systemic inflammatory conditions, such as diabetes, preterm birth, aspiration pneumonia and atherosclerotic cardiovascular disease (Brodala et al, 2005;Liao et al, 2009;Lin et al, 2003;Maekawa et al, 2011;Pussinen and Mattila, 2004). On the cellular level, a convincing body of evidence indicates that P. gingivalis possesses unique signalling properties, which enable it to evade, subvert or manipulate the host immune defences by exploiting the toll-like receptor (TLR) family, in particular TLR2 (Burns et al, 2006;Hajishengallis et al, 2002;Hajishengallis et al, 2008b;Harokopakis et al, 2006;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[39,40] Researches have demonstrated that PG induction may invade endothel and may initiate atherosclerosis in pigs. [75] The presences of PG in atheroma and human carotid aorta had been detected by immunostaining and PCR. [76,77] PG was known to have fimbriae, which allowed it to invade [51] and stimulate host response to produce citokynes, [52,[78][79][80][81] and may be in latent phase [82] to cause chronic infection in EC and SMC.…”
Section: Discussionmentioning
confidence: 99%
“…[76,77] PG was known to have fimbriae, which allowed it to invade [51] and stimulate host response to produce citokynes, [52,[78][79][80][81] and may be in latent phase [82] to cause chronic infection in EC and SMC. [75] Chronic infection was known to be able to cause endothelial dysfunction. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] PG�s fimbriae secretes protein, called gp130, [83] which facilitate PG to invade EC and trigger celluler immune response.…”
Section: Discussionmentioning
confidence: 99%